The Role Of Employee Engagement In Mediating The Effects Of Meaningful Work, Hindrance Stressors, And Work-Life Balance On Quiet Quitting Among Generation Z Employees In Indonesia - Zuliandra Adelia Putri; Barkah Barkah; Rizani Ramadhan; Arman Jaya; Hassanudin Hassanudin (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Quiet quitting has become a major issue in human resource management, changing how Generation Z employees view loyalty. This study looks at whether employee engagement connects meaningful work, hindrance stressors, and work-life balance to quiet quitting among Generation Z workers in Indonesia. Using a quantitative survey, we collected data from Generation Z employees and analyzed it with Structural Equation Modeling (SEM-PLS). The results show some unexpected patterns. Employee engagement did not act as a link, suggesting that enthusiasm for work and the choice to limit workload are not always connected. Only meaningful work was found to reduce quiet quitting, while hindrance stressors had no effect. Another surprising finding was that work-life balance actually increased quiet quitting, suggesting that some employees use withdrawal as a way to achieve balance. Based on these results, organizations should focus less on emotional retention and more on creating meaningful work and clear work boundaries, since high engagement alone does not prevent quiet quitting.